Estratificação de risco pré-operatório e modelagem prognóstica para recorrência e sobrevida em carcinoma hepatocelular após ressecção hepática - Henrique Araújo Lima (2025)
Hepatocellular carcinoma (HCC) commonly arises in the context of chronic liver disease and an impaired underlying liver parenchyma. While the choice of therapeutic strategies is influenced by the complex interplay of these clinical factors, surgery remains the best curative‐intent treatment option. However, recurrence after resection remains a significant challenge due to its high rates and frequent progression to non-transplantable recurrence (NTR). Identifying recurrence patterns, including peak risk rates and recurrence intervals, as well as preoperative risk factors for NTR, is essential to improve outcomes. Moreover, heterogeneity in HCC persists even within established classification systems such as the Barcelona Clinic Liver Cancer (BCLC) staging system. Specifically, the non-recommendation of liver resection for intermediate-stage HCC in the BCLC system remains controversial. This study aims to characterize and analyze the recurrence patterns of HCC while enhancing the granularity of preoperative patient classification. Our goal is to contribute to a better understanding of HCC recurrence patterns and, consequently, refine postoperative surveillance strategies. Furthermore, the findings to be presented may aid in improving the prognosis and outcomes for these patients. Based on international data from large multi-institutional databases, our prognostic models for recurrence and survival also aim to improve preoperative risk stratification, optimizing patient selection for curative-intent liver resection.